1993
DOI: 10.1111/j.1432-1033.1993.tb17717.x
|View full text |Cite
|
Sign up to set email alerts
|

Human pre‐α‐trypsin inhibitor‐precursor heavy chain cDNA and deduced amino‐acid sequence

Abstract: Pre-a-trypsin inhibitor (Pal) is a serine-proteinase inhibitor of M, 130000 found in human serum. This protein belongs to the family of proteins called inter-a-trypsin inhibitor (ITI). Pa1 is composed of a heavy chain (HC3) and of a light chain (bikunin), synthesized by two separate mRNA. Bikunin is identical to the IT1 light chain, the structure of which has already been established. The HC3 is obtained from a precursor called H3. The bikunin is covalently linked to HC3 by a chondroitin-4-sulfate glycosaminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Earlier studies have shown that the heavy chains of pre-and inter-␣-inhibitor are synthesized as precursors with C-terminal extensions, which are cleaved off during transport to the cell surface; for all of these polypeptides cleavage seems to occur between an Asp and a Pro residue (15,16). In the present study we found that incubation at low pH of the precursor of pre-␣-inhibitor heavy chain (proH3) induced cleavage of its C-terminal extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that the heavy chains of pre-and inter-␣-inhibitor are synthesized as precursors with C-terminal extensions, which are cleaved off during transport to the cell surface; for all of these polypeptides cleavage seems to occur between an Asp and a Pro residue (15,16). In the present study we found that incubation at low pH of the precursor of pre-␣-inhibitor heavy chain (proH3) induced cleavage of its C-terminal extension.…”
Section: Discussionmentioning
confidence: 99%
“…The heavy chains are synthesized as precursors with Cterminal extensions of about 30 kDa (15)(16)(17). These fragments are released in the Golgi complex by cleavage between an Asp and a Pro residue (9).…”
mentioning
confidence: 99%
“…4A and 5A) is in agreement with this conclusion. Furthermore, there is a high frequency of the structure-breaking amino acid proline near the C termini of H1 and H2 (39). The fact that the proteinase-sensitive parts of the heavy chains constitute approximately half the polypeptides (see Fig.…”
Section: Fig 5 Partial Proteolytic Degradation Of H2mentioning
confidence: 99%
“…The peptide sequence of the light chain, deduced from that of the cDNA [5,6], corresponds to the precursor of two tandemly arranged proteins, ~l-microglobulin and bikunin (responsible for the protease inhibitory activity), which separate at the time of ITI maturation [7,8]. Three mRNAs coding for distinct heavy-chain peptides, called H1, H2 and H3, were then described [9][10][11]; they showed highly similar amino acid sequences. Further, the ITI-related proteins are synthesized in the liver by four genes located on three different chromosomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…As MBP is a strictly bacterial protein, the anti-MBP activity of these new antisera was unlikely to restrict in any way their use for the analysis of human products and this turned out to be true. Despite the high sequence similarity of ITI heavy chains [11], the anti-MBP-H antisera did not show any cross-reaction between them (Fig. 1).…”
mentioning
confidence: 99%